2016
DOI: 10.1590/0104-07072016001460015
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety Climate at a Private Hospital

Abstract: Evaluate the patient safety climate from the perspective of the health team members at a medium-sized private hospital in a city in the state of Minas Gerais, Brazil and check for relations between the sociodemographic variables and the safety climate scores. This is a descriptive, exploratory and correlational study, conducted with 123 health professionals, with approval from the Research Ethics Committee. Data were collected using the Safety Attitudes Questionnaire. For analysis, we used Student's t-test, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
22
1
7

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 14 publications
5
22
1
7
Order By: Relevance
“…Studies conducted in different Brazilian states using validated instruments revealed weaknesses in assessing the perception of nursing staff of the safety climate (8)(9)(10) . A review of papers on this subject found safety climate assessments in public hospitals (3) , in a private hospital (11) and in public and private hospitals (12) , without correlating the outcomes of these institutions. Therefore, the following question arises: is there a significant difference between the perception of health workers of private and public institutions in relation to the safety climate?…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in different Brazilian states using validated instruments revealed weaknesses in assessing the perception of nursing staff of the safety climate (8)(9)(10) . A review of papers on this subject found safety climate assessments in public hospitals (3) , in a private hospital (11) and in public and private hospitals (12) , without correlating the outcomes of these institutions. Therefore, the following question arises: is there a significant difference between the perception of health workers of private and public institutions in relation to the safety climate?…”
Section: Introductionmentioning
confidence: 99%
“…Women prevailed among Nursing professionals. The health sector has a visible occupation of female labor force, because this sex exceeds 75% of the professionals in this area, particularly concentrating in this professional category 10 . This is similar to another study, which found that job satisfaction also showed maximum mean, 11 a positive point in this context.…”
mentioning
confidence: 99%
“…According to a survey carried out at a hospital in the city of Uberaba-MG, the same domain achieved the average of 59.58 points. 10 This relation results from long workdays, absence of professional training programs, and unavailability of necessary materials, hindering a quality assistance.…”
mentioning
confidence: 99%
See 2 more Smart Citations